1985
DOI: 10.4049/jimmunol.135.2.1281
|View full text |Cite
|
Sign up to set email alerts
|

The association between murine beta 2-microglobulin and HLA class I heavy chains results in serologically detectable conformational changes of both chains.

Abstract: HLA-A3-, HLA-B7-, and HLA-CW3-transfected L cells, maintained in medium supplemented with murine serum so as to ensure that the human heavy chains were associated with murine beta 2-microglobulin, were subjected to a systematic serologic analysis for an evaluation of the structural consequences of such an heterologous association. The hybrid molecules exhibited alterations of their serologic reactivities that suggest the occurrence of structural modifications of both light and heavy chains. Thus, reactivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cancer cells can evade T-cell recognition by downregulating or completely losing MHC class I molecules (34). The structural deficiency of MHC may change the expression of epitopes and increase the expression of β2-MG (35). Chen et al found that a higher level of β2-MG was significantly associated with greater invasion potential and tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells can evade T-cell recognition by downregulating or completely losing MHC class I molecules (34). The structural deficiency of MHC may change the expression of epitopes and increase the expression of β2-MG (35). Chen et al found that a higher level of β2-MG was significantly associated with greater invasion potential and tumor burden.…”
Section: Discussionmentioning
confidence: 99%